Front Cover: Near‐Infrared Spectroscopic Characterization of Cardiac and Renal Fibrosis in Fixed and Fresh Rat Tissue (Anal. Sens. 1/2023). Issue 1 (12th December 2022) - Adegoke, John A.; Gassner, Callum; Sharma, Varun J.; Patel, Sheila K.; Jackett, Louise; Afara, Isaac O.; Raman, Jaishankar; Burrell, Louise M.; Wood, Bayden R.
Abstract : The cover picture shows a handheld near‐infrared spectroscopic probe to detect fibrosis in real time using a murine model. The major differences between spectra of healthy and fibrotic tissue were seen in specific absorption bands, which were attributed to disruption in the collagen network. More information can be found in the Research Article by John A. Adegoke, Jaishankar Raman, Bayden R. Wood, and co‐workers .